Hope as experienced by people with acquired brain injury in a rehabilitation—or recovery process: a qualitative systematic review and thematic synthesis - Højgaard Nejst, Camilla; Glintborg, Chalotte (Frontiers in Rehabilitation Sciences, 2024)
Background There has been an increasing interest in the concept of hope within the field of brain injury rehabilitation. Existing reviews have nevertheless focused on stroke, leaving out the broad population of people with acquired brain injury (ABI). Furthermore a majority of the included studies in those reviews excluded the subgroup of people with communication difficulties, thus primarily giving voice to a select group of people with ABI. Methods A qualitative systematic review was conducted with the purpose of systematically reviewing and thematically synthesise findings about hope as experienced by adults with ABI in a rehabilitation or recovery process. The search strategy included peer-reviewed qualitative studies published after 2000 in English or Scandinavian languages. Searches of EBSCO databases incorporating CINAHL, MEDLINE, and PsycINFO were conducted together with SocINDEX, Social Work Abstracts, Eric and Web of Science. Ten qualitative studies were included, and the Critical Appraisal Skills Program (CASP) was used for assessing the quality and relevance of the ten studies. Qualitative findings were synthesized using Thomas and Harden's methodology. Results Through a thematic synthesis eleven subthemes were identified relating to experiences of hope. These were grouped into four analytical themes: (1) hope a two folded phenomenon; (2) time and temporality; (3) progress, goals and visibility and (4) the alliance; a balancing act requiring good communication skills. Conclusion This review has shown that even though hope has both a positive and negative side to it, it is necessary as a driving force for people with ABI in terms of supporting them to keep going and not give up. Rehabilitation professionals are advised to embrace the ambiguity of hope, customizing the support of hope to each person with ABI. Attention is needed on how to make progress visible for persons with ABI during their rehabilitation process just as rehabilitation professionals should acknowledge the alliance with the person with ABI as a core component of rehabilitation. This requires a focus on professionals' communication skills if hope promoting relationships between professionals and persons with ABI are to be achieved.